Case Report: Child with Menkes syndrome complicated by bladder diverticula - Wu, Guoxing; Gao, Pengfei; Zhang, Wenbin; Li, Honghui; Li, Zhaoying; Wu, Ruifa; Li, Zuoqing; Huang, Mingchuan; Xu, Zhe (Frontiers in Pediatrics, 2025)
BackgroundMenkes syndrome is a rare X-linked genetic disorder of copper metabolism caused by variants in the ATP7A gene. It is characterized by developmental delay, hair abnormalities, hypotonia, and organ dysfunction. Bladder diverticula are a rare but recognized urological complication, and its rupture can lead to severe clinical consequences.MethodsWe report a case of a 3-year-old boy diagnosed with Menkes syndrome, presenting with multiple bladder diverticula and diverticular rupture, resulting in acute abdominal effusion. The patient underwent excision of multiple bladder diverticula guided by imaging and urodynamic evaluation. Postoperative functional recovery was assessed through follow-up imaging and urodynamic studies.ResultsPostoperative urodynamic parameters showed significant improvement. Follow-up revealed satisfactory voiding function without evidence of recurrence or increased residual urine. Imaging and urodynamic studies were instrumental in both preoperative localization and postoperative functional assessment.ConclusionsEarly diagnosis and surgical excision of bladder diverticula in patients with Menkes syndrome can significantly improve prognosis. Imaging and urodynamic studies provide reliable support for comprehensive management and are invaluable for long-term postoperative follow-up.